1966
DOI: 10.1113/jphysiol.1966.sp007988
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory action of noradrenaline and other monoamines on spinal neurones

Abstract: SUMMARY1. L-Noradrenaline (NA), 5-hydroxytryptamine (5-HT) and acetylcholine (ACh) were administered micro-electrophoretically to feline lumbar neurones while recording their spike potentials extracellularly.2. There was no evidence to suggest that NA acts as an excitatory transmitter in the spinal cord.3. NA had potent inhibitory effects on some interneurones as revealed by a depression of spontaneous and synaptic firing and on the firing to a local application of an excitant amino acid. The effects on Rensha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

1967
1967
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(54 citation statements)
references
References 22 publications
3
50
1
Order By: Relevance
“…In particular, the number of cells responding to particular potential transmitter substances may be markedly reduced and the pattern of responses to them distorted by anaesthetics. Engberg & Ryall (1966) and Weight & Salmoiraghi (1966) observed that 5-HT and noradrenaline did have effects on spinal cord neurones in decerebrate cats and they suggested that it was the use of anaesthetics in the experiments of and Curtis (1962) which had probably been responsible for their failure to observe similar effects. The number of 5-HT sensitive cells in spinal cord was reduced threefold by the use of ether (Weight & Salmoiraghi, 1966).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the number of cells responding to particular potential transmitter substances may be markedly reduced and the pattern of responses to them distorted by anaesthetics. Engberg & Ryall (1966) and Weight & Salmoiraghi (1966) observed that 5-HT and noradrenaline did have effects on spinal cord neurones in decerebrate cats and they suggested that it was the use of anaesthetics in the experiments of and Curtis (1962) which had probably been responsible for their failure to observe similar effects. The number of 5-HT sensitive cells in spinal cord was reduced threefold by the use of ether (Weight & Salmoiraghi, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the balancing current to the control barrel when it contained sodium bimaleate also meant that there was no change in the rate of ejection of maleate anions when 5-HT was 5-HT AND CORTICAL NEURONES 273 ejected (cf. Engberg & Ryall, 1966). This excluded the possibility that 5-HT effects were an artifact resulting from the removal of the backing current which had been expelling the potentially potent anion, maleate.…”
Section: Methodsmentioning
confidence: 99%
“…The direct application of 5-HT onto spinal interneurones or motoneurones by microiontophoresis has usually caused either the depression of cell excitability or has been without effect (Curtis, Phillis & Watkins, 1961;Engberg & Ryall, 1966). Two studies, however, have noted the occurrence of infrequent excitatory responses (Weight & Salmoiraghi, 1966;Phillis, Tebecis & York, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The interneurone population depressed by microiontophoretically applied PMPEA, so far as it has been identified, coincides well with the population influenced by NA (Engberg & Ryall, 1966) and by intravenous PMPEA (Jordan & Willis, 1973). The depressant effects of NA, 5-HT and PMPEA, when they were observed on identified neurones (orthodromically activated neurones, Table 1), were limited to interneurones activated by flexion reflex afferents.…”
Section: Discussionmentioning
confidence: 94%